Hospitalization trends for cardiovascular diseases in Manaus-Amazonas (Research, Society and Development, 2022)
Cardiovascular diseases are currently a global health problem that has negatively affected public resources. These diseases are responsible, every month, for a large number of hospitalizations, which seem to have increased over the years. The aim of this study was to examine the trends in hospitalizations for adult cardiovascular diseases in the city of Manaus-AM. This is an epidemiological study based on the analysis of DATAUS data from 2015 to 2020, referring to hospitalizations for Arterial Hypertension (AH), Acute Myocardial Infarction (AMI) and Heart Failure (HF) in adults in the city of Manaus. . In the year 2015 to 2020, 17,634 hospitalizations were recorded, computed for AH (12.7%), HF (51.8%) and AMI (35.5%), generally higher in males (>50.0%). While hospitalizations for AH remained stable between 2015 and 2020 in both sexes, there was a trend of decline of 12.3 percentage points in hospitalizations for HF. On the other hand, trends in hospitalizations for AMI increased by 20.1 percentage points. In this study, men were hospitalized more than women for all pathologies. In addition, there was a positive decline in hospitalizations for HF, and an increase in hospitalizations for AMI. Health promotion and AMI prevention measures need to be prioritized, especially among men in Manaus.